Predictors of turnover intention among multinational corporation employees - Lim, Xin Jean; Lim, Pang Im; Ng, Siew Imm; Yee, Wong Foong (Inderscience, 2021)
The main objective of this study was to understand the impacts of job satisfaction, organisational commitment, job stress, and safety climate on turnover intention among Malaysian employees working in multinational corporations (MNCs). A total of 130 valid responses were collected from MNC employees through both online and offline surveys. The data was then analysed using partial least squares structural equation modelling (PLS-SEM). Notably, our findings showed that job satisfaction and organisational commitment are negatively related to turnover intention, while job stress is positively related to turnover intention. The outcomes of this study provide valuable insights to practitioners, particularly in reducing the turnover rate in MNCs.